PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING (SFE) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS XI IPA SMAN 1 KATEMAN INHIL - Novaliana '; Susilawati '; Erviyenni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: The research aims to increase student learning achievement on the subject structure of atoms and the periodic system of elements in class XI science SMAN 1 Kateman Inhil. This research was of experiment research with pretest-posttest design. The samples of this research were the XI science 1 as the experimental group and XI science 2 class as the control group. In experimental group was applied cooperative learning type Student Facilitator and Explaining model, while the control class was not. Data analysis technique used is the t-test. Based on analysis data tcount>ttable is 4,83 > 1,67, means that the application of model cooperative learning type Student Facilitator and Explaining can improve student achievement on the subject structure of atoms and the periodic system of elements in class XI science SMAN 1 Kateman Inhil by category increase achievement (N-Gain) high at 0.72.Keywords: Learning Achievement, Cooperative type Student Facilitator and Explaining, Atomic Structure and Element of the Periodic System.